Makeup Artist Communication Mix Model in Jakarta - Ekasari, Raudha Putri; Irwanti, Marlinda; Bungin, Burhan; Jamalullail, Jamalullail (PT. Riset Press International, 2024)
Makeup Artist as a business-to-consumer (B2C) that focuses on providing direct services to individual clients. Since the Covid-19 pandemic, digital marketing has been increasingly relied upon to reach users. Content optimization through social media is an effective strategy in reaching users. Through phenomenology involving a number of prominent Makeup Artists in Jakarta, this research explores the use of Communication Mix tools used by Makeup Artists in marketing their services. A qualitative research method with color coding was used for the case studies in this research. The Communication Mix is the main object of this research, while the leading Makeup Artists in Jakarta will be the subject of the research. Data will be collected through in-depth interviews and content from social media used by makeup artists. From the results of data analysis using color coding on interview transcripts, from 6 (six) Communication Mixes: 1) Advertising, 2) Public Relations, 3) Sales service/agents/remote marketing, 4) Events, activities, and meetings, 5) Word of Mouth, 6) Sales Promotion, only 4 (four) are maximally used by Makeup Artists. No one Communication Mix tool can stand alone. Instead, a strategic combination of all four Communication Mix tools, namely: 1) Advertising, 2) Sales Promotion, 3) Public Relations, and 4) Word of Mouth, can create a very strong synergistic effect in expanding the reach and increasing the success of the Makeup Artist's business and can be maximally used by the Makeup Artist for services and acquiring potential clients.